ULTRASOUND STUDY OF PATIENTS WITH KNEE ARTHROSIS - Dalerova Madina Farrukhovna, Mirkhakimova Fariza Mirkhamzaevna (Miasto Przyszłości, 2024)
The essence of this scientific article is that Osteoarthrosis is a common degenerative joint disease, early changes in the joint, the etiology of knee and hip osteoarthritis and many other information.